A queda de Gringo: sobre o amor de transferência em um hospital psiquiátrico - Rizzo, Amanda Teixeira (2017)
This dissertation utilizes as a fundamental point of investigation a clinical enigma experienced during a psychoanalytic care in a psychiatric hospital. The case is of a patient who in his third hospitalization, to treat his symptoms of alcohol and drug abuse, manifested a type of transference different from previous treatments. We observed the establishment of transference love which was adopted as the conductor of the analysis. One question summons us to the research: what was different about this third hospitalization? From this clinical experience we gather repercussions in the conduction of the analysis and also the life of the patient both which requested a more specific investigation of the psychoanalytic concepts of identification and incorporation, since the reveal of “Gringo’s” existence as an identification figure after the impact of an interpretation. Thus a clinical-theoretical discussion is presented aiming to articulate the issues raised by the case and its implications to the psychoanalytic clinic in regards to treatments offered by psychiatric institutions specifically concerning the field of chemical dependency